A Survey on Intelligence Data Analysis: Issues and Challenges - Pankaj Saxena, (AG Volumes, 2022)
Many real-world applications now need automated or semi-automatic analysis of the data, which has given rise to the new area of (IDA) "intelligent data analysis," which combines several disciplines, including artificial intelligence and statistics in particular. As a whole, they work well together: Computing power is not a replacement for statistical understanding when it comes to statistical procedures for huge data sets. As a result, data analysis systems are becoming more sophisticated. When analysing data, there are a broad variety of issues that might arise. This article discusses some of these issues and provides possible solutions. Using data from a real-world level crossing risk assessment scenario, we investigate some of these issues and ideas.